PENYULUHAN PENTINGNYA KOMUNIKASI DALAM MEMBENTUK LINGKUNGAN SOSIO-EMOSIONAL DALAM PENGELOLAAN DESA WISATA PADA REMAJA DI DESA BAYUNGGDE KECAMATAN KINTAMANI KABUPATEN BANGLI - Nur Kholifatur Rizqi Maulina Sudibyo; Luh Hendra Kusuma Dewi; Nurul April Yani; I Gusti Ketut Arya Sunu (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2021)
This counseling activity is a social sensitivity program that aims to build communication in order to form a socio-emotional environment in teenagers in Bayunggede Village, Kintamani District, Bangli Regency. Teenagers in Bayunggede Village are given an understanding of communication in order to conduct good communication activities in shaping the emotional social environment in the midst of the community that is currently undergoing many changes due to the covid 19 pandemic. This activity emphasizes the communication material as a real manifestation of the youth in building their village through a touching and caring effort and sensitive to the phenomena that have occurred lately. The implementation of activities is carried out face-to- face FGD (Focus Group Discussion) and documentation using health protocols.